Virologic and immunologic status of children with HIV-TB co-infections - Djatnika Setiabudi; Citra Cesilia; Almira Aliyannissa; Heda Melinda Nataprawira (Paediatrica Indonesiana, 2021)
Background Studies about virologic and immunologic status of HIV children are lacking. Tuberculosis (TB) is the most common opportunistic infection in HIV patients and co-infection is associated with much worse prognosis. Objective To describe the virologic and immunologic status of patients with HIV and TB co-infection, before and after HIV and TB treatment. Methods A prospective study was conducted in HIV co-infected with TB patients in an Indonesian tertiary hospital between November 2016—December 2018. Viral load and CD4 levels were performed at diagnosis and after 6 months of HIV and TB treatment. Results Of 44 children hospitalized due to HIV, 15 newly diagnosed HIV cases had TB co-infection. Thirteen were included as subjects. Most patients (10/13) were under 5 years of age, with similar female and male proportions (7/13 vs. 6/13, respectively). All were diagnosed with stage 4 HIV. Six patients had respiratory problems at admission. First examinations revealed severe immunodeficiency (CD4+ <20%) in all patients, and high viral loads (>105 copies/mL) in most (9/13) patients. Despite good compliance to medications, 8/13 patients died before the sixth month follow-up. Deterioration of virologic and immunologic status was seen in 3/4 of the followed-up patients. Conclusion Children with HIV-TB coinfections have severe immunodeficiency and high viral loads. Most such patients die before 6 months, while survivors experience virologic and immunologic status deterioration. Future study must take into account for HIV drug resistance investigation.